Effects of Hedranthera barteri Root Extract on Gastric Emptying and Intestinal Motility in Wistar Rats (African Journal of Biomedical Research, 2020)
Hedranthera barteri leaf extracts have been reported in folk medicine to have laxative properties amongst its many other therapeutic potentials. This study was therefore carried out to investigate the effects of Methanol extract of Hedranthera barteri (MEHBR) root on gastric emptying and intestinal motility in albino rats. The methanol extract of H. barteri (MEHBR) was obtained by cold extraction and stored at 4°C. Forty-eight female rats weighing (180-200g) were randomly divided into two groups of 24 rats each based on the parameters being assessed (gastric emptying and intestinal motility). Each subgroup was divided into four groups of six rats each as follows:  Group 1, the control group, was given normal saline while animals in groups 2, 3 and 4 were treated with 50mg/kg, 100mg/kg and 200mg/kg of MEHBR respectively. Gastric emptying was assessed using the glass beads method and gastrointestinal motility was assessed as a measure of the percentage change in gastrointestinal transit time using the charcoal meal method. A decrease in gastric emptying rate was observed in the rats treated with MEHBR at 50mg/kg (P < 0.05) when compared to control rats while values obtained in the 100mg/kg and 200mg/kg MEHBR treated rats indicate a significant increase in gastric emptying rate. Intestinal motility increased in a dose dependent manner with the 50mg/kg, 100mg/kg and 200mg/kg exhibiting percentage gastrointestinal transit time of 47.3 ± 5.5%, 35.7 ± 5.2% and 23.3 ± 3.0% respectively. Methanol root extracts of Hedranthera barteri decreases gastric emptying rate at low dose and increases gastric emptying at high doses. H. barteri also increases gastrointestinal motility in a dose dependent manner with 200mg/kg treatment exhibiting the highest laxative effect.